Peningkatan Keterampilan Pemahaman Membaca Pemahaman Peserta Didik Menggunakan Strategi Directed Reading Thinking Activity (DRTA) di Kelas V UPTD SDN 03 Kabupaten Simalanggang 50 Kota - Az Zahra, Fathia; Azima, Nana Fauzana; Suriani, Ari; Chandra, Chandra (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the improvement of students' reading comprehension skills through the Directed Reading Thinking Activity (DRTA) strategy. The type of research used is Classroom Action Research (PTK) with stages of planning, implementation, observation, and reflection. This research was carried out in two cycles with the research subject of grade V students of UPTD SDN 03 Simalanggang, which consisted of 20 students. The results of the research conducted showed an increase in cycle I to cycle II, namely the percentage of average assessment of teaching modules in cycle I meeting 1 was 82%, cycle I meeting 2 increased to 89%, and in cycle II it increased to 96%. The average assessment percentage of teacher aspects in cycle I meeting 1 was 75%, cycle I meeting 2 increased to 83%, and in cycle II it increased to 96%. The average assessment percentage of student aspects in the first cycle of meeting 1 was 82%, the first cycle of meeting 2 increased to 85%, and in the second cycle it increased to 96%. The average assessment of students' reading comprehension skills in the first cycle of meeting 1 was 70.75, the first cycle of meeting 2 increased to 80.32, and in the second cycle it increased to 90.2. Thus, the implementation of the Directed Reading Thinking Activity (DRTA) strategy can improve students' reading comprehension skills in elementary schools